The Implementation of Aqidah Akhlak (Islamic Moral and Faith) Learning in Forming the Character of Students in Madrasah Aliyah Binjai - Mahyuni, Sri; Tanjung, Ellisa Fitri (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2024)
This paper aims to find out how the process of implementing Islamic moral and faith (aqidah akhlak) learning and how the method of habituation and da'wah in character building along with supporting and inhibiting factors in the learning process. This research used qualitative research. Data collection techniques were carried out using interview, observation, and documentation methods. The data analysis technique was data processing and data analysis which was field data analysis. The results of this study included (1) The implementation of Islamic moral and faith (aqidah akhlak) learning at Madrasah Aliyah Aisyiyah Binjai was carried out properly by the applicable curriculum by referring to the lesson plans used consisting of opening, core, and closing activities. (2) The method of habituation and da'wah had been going well by applying the method of habituation by getting used to good qualities so that students were accustomed to good morals and character. While the da'wah method could also make students better at learning. (3) Supporting factors in the implementation of Islamic moral and faith (aqidah akhlak) learning were parents. While the inhibiting factor was the lack of support from parents for the education of students and the family economy. (4) The effect of implementing the habituation and da'wah method in learning Islamic moral and faith was to bring a good influence such as students were more disciplined and active in learning, respectful and polite to teachers and parents, and getting used to obeying the rules that exist in school and no more students engaging in conflict.